2005
DOI: 10.1093/humrep/deh696
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent pregnancy failure is associated with a polymorphism in the p53 tumour suppressor gene

Abstract: Our results indicate an over-representation of the Pro allele of the p53 gene in women with IRM, giving support to the theory that p53 has a potential role during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 17 publications
1
46
1
Order By: Relevance
“…The frequency of homozygous Pro/Pro genotypes was found significantly higher among the women with RPL than the other two groups indicated that p53 codon 72 polymorphism would be expected to play a major role to bring about RPL [22]. In Pietrowski study, an overrepresentation of the Pro allele of the p53 gene in women with idiopathic recurrent miscarriages supports to the theory that p53 has a potential role during pregnancy [27]. On the contrary, the other studies reported an insignificant association between the Pro allele and RPL [24,28].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The frequency of homozygous Pro/Pro genotypes was found significantly higher among the women with RPL than the other two groups indicated that p53 codon 72 polymorphism would be expected to play a major role to bring about RPL [22]. In Pietrowski study, an overrepresentation of the Pro allele of the p53 gene in women with idiopathic recurrent miscarriages supports to the theory that p53 has a potential role during pregnancy [27]. On the contrary, the other studies reported an insignificant association between the Pro allele and RPL [24,28].…”
Section: Discussionmentioning
confidence: 75%
“…G1 arrest or the potential to resist apoptosis might be the explanation that Pro/Pro carriers are more associated with RPL than with Arg allele carriers. However, these possible explanations are largely speculative and more studies on how the p53 Pro variant contributes to the complex pathogenesis of RPL is required [27].…”
Section: Discussionmentioning
confidence: 99%
“…Pietrowski and colleagues (2005) [46] reported an association of the P72 allele and recurrent miscarriages. However, Fang and colleagues (2011) [16] did not find any difference in genotype and allele frequency of TP53 P72 and R72 forms through a case-control study involving women with miscarriages.…”
Section: Discussionmentioning
confidence: 99%
“…This polymorphism seems to increase the chance of miscarriage in healthy women [46]. Thus, it is possible that genes that undergo selection in the TP53 pathway may affect human reproduction [29].…”
Section: Discussionmentioning
confidence: 99%
“…Carriership of the TP53 72Pro allele is overrepresented among women with idiopathic recurrent miscarriage [41,87] and in women with recurrent implantation failure after IVF and embryo transfer [45,88]. In the latter study, the pregnancy rates after IVF were reported to be close to 70 % for women with genotypes containing at least one 72Arg allele (Arg/ Arg or Pro/Arg) vs. 33 % for women with homozygous Pro/Pro genotypes; the embryo implantation rates were 33 % for women with 72Arg-containing genotypes vs. 7 % for women with Pro/Pro genotypes; and ongoing pregnancy rates were 53 % for women with 72Arg-containing genotypes vs. 14 % for women with Pro/ Pro genotypes.…”
Section: Reproductive Outcomes and Individual Repair Capacitymentioning
confidence: 99%